Test report no. PLBO/15 intermittent cutting tests with tools of RD107, RD110 and SIP, having radiused cutting edges - College of Aeronautics, (Cranfield) (College of Aeronautics, 1965)
Tools of grade S1P„ RD1O7 and RD11O with radiused cutting edges were tested to failure cutting slotted bars of EN9 at 600 f.p.m., 0.010 in/rev. feed and 0.10 in depth of cut. The results showed that there was a reduction in the frequency of early tool failure as compared with unradiused tips. A statistical analysis showed that there was no significant difference between the mean tool lives of the three grades.